Seasonal Pattern of Hand Foot and Mouth Disease in an Out-patient Clinic of a Tertiary Care Pediatric Hospital, Dhaka (Northern International Medical College Journal, 2021)
Background : Hand, foot and mouth disease (HFMD) is a contagious disease of children, occurs primarily under five years of age, characterized by a history of brief febrile illness and a typical skin rash over hands and feet with or without sores in mouth, caused usually by Coxsackie virus[1]A16 viruses. It is mainly the disease of tropical and subtropical countries and bears a complex-relation with meteorological variables like temperature, rainfall and relative humidity, although no study has yet been done in Bangladesh to explain the complex relationship of the disease with these variables.Objective : This study sought to describe the occurrence of HFMD and its association with meteorological factors in Dhaka city.Methods : The present cross-sectional study collected data of 231 HFMD cases from the records of the daily register of Out-patient Department of Dhaka Shishu Hospital, Dhaka between January 2018 to December 2019. According to the study protocol a child was identified as having HFMD who had a history of brief febrile illness accompanied by a typical skin rash with or without mouth ulcers. Total numbers of cases treated monthly at OPD during the period were also recorded. Meteorological data were provided by Bangladesh Meteorological Department, which among others, included monthly average temperature, relative humidity and amount of rainfall. While the outcome variable was monthly number of HFMD cases, the predictive variables were average temperature, humidity and rainfall during the study period.Results : Majority (85.3%) children in the present study was < 5 years old. A male preponderance was observed in the series (60%) with male to female ratio being 3:2. A clustering of HFMD cases was observed to occur between June to October when monthly average temperature, total rainfall and humidity all were at their maximum compared to those found between November to April. The clustering of cases was more intense in the year 2019 than that in the year 2018. During the period average monthly temperature was 29.20C, average rainfall was 62.6% (238 mm) of the total annual precipitation and mean relative humidity was 79%. The proportion of HFMD cases out of total cases treated during the period was 2.2% in 2018 and was 4.1% in 2019, which in the dry season (November to April) was 0.4% and 0.5% in 2018 and 2019 respectively.Conclusions : The study concluded that majority of the HFMD cases occur under five years of age and boys are more likely to have the infection than the girls. A seasonality of HFMD occurrence is observed with a higher number of cases occurring in the monsoon season and fewer cases in the dry season.Clustering of HFMD cases occur between May to October when monthly average temperature, total rainfall and humidity all are at peak compared to those in November to April of the year.Northern International Medical College Journal Vol.11 (2) Jan 2020: 453-457